(untitled) (Journal of Economic Research & Business Administration, 2018)
This article suggests theoretical-methodological and scientific-practical basis to transition of low-carbon economy in the key sectors of the Republic of Kazakhstan. In the framework of the development of the theoretical and methodological foundations of a low-carbon economy, the authors proposed the definition of a category of a «low-carbon» economy. Based on methodology preconditions potential low-carbon development and the basic industries of the national economy were defined. Authors analyzed a present situation with the consumption of energy resources and indicators of energy intensity of Kazakhstan’s GDP in mining and energy sectors and develop recommendations for the future transition to low carbon of the basic industries of national economy. In the article the authors propose approaches to the assessment of the carbon potential of the basic sectors of the economy in the implementation of the Paris Climate agreement. Using the indicator approach and economic and mathematical modeling, the authors propose forecast scenarios of emissions growth in sectors energy and transport. It is concluded that the main sectors of the economy of the Republic of Kazakhstan have great potential for the transition to low-carbon development.